Sago as a Prebiotic to Increase Short-chain Fatty Acid Production in The Digestive Tract - Catarina Aprilia Ariestanti; Joey Alessandro Wijaya (University of Sultan Ageng Tirtayasa, 2026)
Sago (Metroxylon sagu) is a locally abundant source of resistant starch (RS) found in eastern Indonesia. Resistant starch has attracted considerable attention because it resists enzymatic digestion in the small intestine and serves as a fermentation substrate for gut microbiota in the colon. As a dietary intervention, RS has been reported to modulate gut microbiota composition and enhance short-chain fatty acid (SCFA) production, indicating its potential as a prebiotic. This review examines the characteristics and potential of sago-derived RS as a prebiotic, particularly its role in modulating gut microbiota and increasing SCFA production, based on literature retrieved from major scientific databases. Articles were selected using predefined inclusion and exclusion criteria and keyword-based screening to evaluate the role of sago RS in gut microbial fermentation and SCFA formation. Studies indicate that sago contains high levels of RS, with a prebiotic index (PI) value of +12.19, higher than fructooligosaccharides (FOS) (+9.45) and inulin (+6.82) after 24 h of incubation in in vitro experiments. In vivo studies using high-fat diet-induced rats have also shown that sago RS is selectively fermented by beneficial Lactobacilli and Bifidobacteria, leading to increased SCFA concentrations. Evidence from both in vitro and animal studies suggests that RS may influence gut microbiota composition and SCFA production. However, most available evidence remains limited to laboratory and animal studies. Therefore, further comprehensive studies are needed to validate its effectiveness and support the development of sago as a locally sourced functional prebiotic food.